Analisis Penerapan PSAK 105 Dalam Transaksi Pembiayaan Mudharabah Pada Studi BMT Mandiri Abadi Syariah Kecamatan Medan Denai Kota Medan - Ofrahaza Siregar; Tuti Anggraini; Arnida Wahyuni Lubis (Jurnal Iqtisaduna, 2024)
Institutions like Islamic cooperatives, Islamic pawnshops, and Baitul Maal Wa Tamwil (BMT) are garnering public attention. As an Islamic financial institution, BMT collects community funds and redistributes them through financing and loans to boost the regional economy. This study aims to understand the implementation of mudharabah financing and the application of its characteristics, recognition, measurement, presentation, and disclosure according to PSAKNo.105 at BMT Mandiri Abadi Syariah. The study collects data from interviews and documentation on accounting practices in mudharabah financing at BMT Mandiri Abadi Syariah using a qualitative descriptive approach based on PSAK105. The study's findings reveal that: 1) The recognition of mudharabah financing at BMT Mandiri Abadi Syariah needs to be fully compliant with regulations due to inadequate record-keeping when customers delay payments. 2) The measurement of mudharabah financing is deemed appropriate, utilizing cash-based recording upon receipt of payments. 3) The presentation of mudharabah in financial statements needs to be revised, failing to reflect actual values. 4) The disclosure of mudharabah is accurate, providing relevant information about transactions as required. 5) While the recognition, measurement, and disclosure of mudharabah transactions align with PSAK 105 regarding measurement and disclosure, there are still issues with recognition and presentation, needing to adhere to standards fully.